Answers

2015-09-14T11:37:40+05:30
Take x common..then it will become quadratic equation
0
The Brainliest Answer!
  • Brainly User
2015-09-14T12:34:24+05:30
Given=>3x³−x²−10x

Solution=>
3x³−x²−10x

3x³−x²−(2.5)x ----We need to factor the GCF (Greatest Common Factor).The resulting term is a productof the GCF and the original expression divided by the GCF.


x(3x
³  −  x² 2·5x)
    x         x        x
x(x−2)(3x+5)

So answer will be =>
x(x−2)(3x+5)

 
2 5 2
PLZ COMMENT ON MY ANSWER
thanks for the answer
your welcummmm my pleasureeee